STRATEGI PENINGKATAN KUALITAS PELAYANAN KTP-el DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MALAKA: - Petrus Vinansius Tangging; Frans Bapa Tokan; Eusabius Separera Niron (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This research is titled Strategy for Improving the Quality of KTP-el Services at the Population and Civil Registration Office of Malaka Regency. The main objective of this research is to describe the strategy for improving the quality of KTP-el services at the Population and Civil Registration Office (Dukcapil) of Malaka Regency. The research method used is descriptive with a qualitative approach, utilizing interview, observation, and documentation techniques. The research findings indicate that Dukcapil Malaka has successfully implemented the principles of transparency, responsibility, and equality in KTP-el services. However, challenges in improving efficiency and accessibility in remote areas still need more attention. Moving forward, further efforts are required to expedite services, expand the online system, and enhance socialization to ensure more efficient, faster, and equitable services for the entire community.